Is there an association between microbial exposure and food allergy? A systematic review. Issue 4 (11th April 2013) - Marrs, Tom; Bruce, Kenneth D.; Logan, Kirsty; Rivett, Damian W.; Perkin, Michael R.; Lack, Gideon; Flohr, Carsten
Abstract The environmental factors driving the recent increase in the prevalence of food allergy (FA) are unclear. Since associations have been demonstrated between microbial exposure and the likelihood of eczema and respiratory allergies, we reviewed the evidence for FA. Medline was systematically searched from inception to the end of July 2012 for studies investigating links between FA and environmental exposures, likely to influence microbial exposure, such as Caesarean delivery, family size, day‐care attendance, childhood infections, immunizations and antibiotic use. We selected studies reporting food challenge data, reported doctor‐diagnosed (RDD) FA and food sensitization. Methodological differences and study heterogeneity precluded meta‐analysis. A total of 46 studies were identified, of which 28 (60.9%) were prospective and 13 (28.3%) used food challenges to diagnose FA. Caesarean delivery was investigated in 13 studies, of which three infant cohorts demonstrated an increase in challenge‐proven FA (one cohort) and food sensitization (two cohorts), and one cross‐sectional study reported increased RDDFA. Four studies investigated the effect of having siblings, with one infant cohort demonstrating less challenge‐proven FA and a cross‐sectional study showing a decrease in RDDFA. Attending childcare before 6 months was associated with less challenge‐proven FA in one cohort. A cross‐sectional survey identified an inverse relationship between hepatitis A serology and peanut sensitization. One of eleven trials investigating probiotics demonstrated a quicker acquisition of milk tolerance amongst allergic infants. Factors influencing microbial exposure may be partly responsible for rising FA burden, but further prospective studies using double‐blind placebo controlled food challenges as an outcome are required.